2022
DOI: 10.1021/acs.estlett.2c00193
|View full text |Cite
|
Sign up to set email alerts
|

Widespread N-(1,3-Dimethylbutyl)-N′-phenyl-p-phenylenediamine Quinone in Size-Fractioned Atmospheric Particles and Dust of Different Indoor Environments

Abstract: Transformed from the antioxidant N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6-PPD), the emerging toxicant 6-PPD quinone (6-PPDQ) has received extensive attention because of its potential toxic effects. However, evidence on the size distribution patterns of atmospheric particles and environmental occurrence remains limited. We determined 6-PPDQ pollution levels in eight size-segregated particles (0.43–10 μm) from four waste recycling plants and dust samples from six typical indoor compartments in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…A more recent study provided new evidence of multiple PPD-derived quinones in environmental media . These selected PPDs and their derived quinones have also been verified to be toxic and pervasive in the environment. In contrast to PPDs, NPAs and DPAs have rarely been investigated, and most have not yet entered the radar of toxicity or environmental studies. Generally, environmental PPDs, NPAs, and DPAs are considered to be linked to tire rubber. ,,, Comprehensive identifications of AAs, including PPDs, NPAs, and DPAs, as well as their significant sources other than tire rubber, are urgently needed to assess the overall risk.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study provided new evidence of multiple PPD-derived quinones in environmental media . These selected PPDs and their derived quinones have also been verified to be toxic and pervasive in the environment. In contrast to PPDs, NPAs and DPAs have rarely been investigated, and most have not yet entered the radar of toxicity or environmental studies. Generally, environmental PPDs, NPAs, and DPAs are considered to be linked to tire rubber. ,,, Comprehensive identifications of AAs, including PPDs, NPAs, and DPAs, as well as their significant sources other than tire rubber, are urgently needed to assess the overall risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the detailed toxicity mechanism of 6PPD-Q is still unknown. Zhang et al investigated human exposure to 6PPD-Q via inhalation using simulations and demonstrated an accumulation of the contaminant in the upper respiratory tract . Recently, our study has revealed a series of other PM 2.5 -bonded PPD-quinones in addition to 6PPD-Q, which also ubiquitously occurred in urban runoff and roadside soil .…”
Section: Introductionmentioning
confidence: 51%
“…Zhang et al investigated human exposure to 6PPD-Q via inhalation using simulations and demonstrated an accumulation of the contaminant in the upper respiratory tract. 21 Recently, our study has revealed a series of other PM 2.5 -bonded PPDquinones in addition to 6PPD-Q, which also ubiquitously occurred in urban runoff and roadside soil. 20 Given that atmospheric quinones are an important redox-active component that would cause oxidative stress in living organisms, it is highly possible that these emerging quinones could contribute to a certain amount of OP caused by PM 2.5 .…”
Section: ■ Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, an environmental transformation product of a phenyldiamine-based tire rubber antioxidant additive (6PPD quinone) was recently linked to mass mortalities of salmon returning to spawn in the U.S. Pacific Northwest . It and precursors have also been detected in indoor dust, especially within vehicles . Another example of unintentionally produced contaminants, PFAS residuals, arose from treatment of high-density polyethylene pesticide storage containers with fluorine gas (to reduce their permeability)…”
Section: Trends In Global Chemical Production and Environmental Conta...mentioning
confidence: 99%